2014
DOI: 10.1002/ajpa.22567
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal manifestations of stress in child victims of theGreatIrishFamine (1845–1852): Prevalence of enamel hypoplasia, Harris lines, and growth retardation

Abstract: The Great Irish Famine of 1845-1852 is among the worst food crises in human history. While numerous aspects of this period have been studied by generations of scholars, relatively little attention has so far been given to the physiological impact it is likely to have had on the people who suffered and succumbed to it. This study examines the prevalence of enamel hypoplasia, Harris lines, and growth retardation in the nonadult proportion of a skeletal population comprising victims of the Famine who died in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 62 publications
1
48
0
Order By: Relevance
“…The pattern, however, is also present in two attritional burials, though the pattern is less distinct, and is observed in individuals without evidence of EH formation; thus we cannot definitively associate opposing covariance of δ 13 C and δ 15 N with nutritional stress that is sufficient to cause EH. An analysis of EH and incremental dentine profiles of individuals who experienced the Great Irish Famine (1845–1852) observed that the least amount of EHs formed during famine compared with before and after the event (Geber, 2014), indicating that nutritional stress may not necessarily result in EH.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern, however, is also present in two attritional burials, though the pattern is less distinct, and is observed in individuals without evidence of EH formation; thus we cannot definitively associate opposing covariance of δ 13 C and δ 15 N with nutritional stress that is sufficient to cause EH. An analysis of EH and incremental dentine profiles of individuals who experienced the Great Irish Famine (1845–1852) observed that the least amount of EHs formed during famine compared with before and after the event (Geber, 2014), indicating that nutritional stress may not necessarily result in EH.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings indicated that children in the lower classes were under the greatest levels of physiological stress, but the upper classes were not immune to such stressors, probably as a result of trends in child rearing practices rather than poverty. A similar approach which used multiple indicators, this time Harris lines, linear enamel hypoplasia, growth disturbances and cribra orbitalia, was undertaken by Geber (2014) in his study of children who died in the Great Irish Famine of the nineteenth century. The signs of physiological stress evident in these juveniles would undoubtedly have been associated with malnutrition and infections related to the famine.…”
Section: The Palaeopathology Of Childhoodmentioning
confidence: 99%
“…Enamel hypoplasia is linked to celiac disease in some patients (Smith and Miller 1979;Wierink et al 2007) but as a non-specific stress indicator. It is also linked to environmental and societal stressors such as food shortage (Geber 2014), weaning (Ash et al 2016) and birth weight (Nelson et al 2013). Enamel hypoplasia can also be a hereditary condition (Robinson, Miller, and Worth1966).…”
Section: Celiac Disease Inferred From Pathological Morphologymentioning
confidence: 99%